2004
DOI: 10.1345/aph.1d360
|View full text |Cite
|
Sign up to set email alerts
|

Possible Gatifloxacin-Induced Hyperglycemia

Abstract: The temporal relationship between gatifloxacin administration and the patient's hyperglycemia suggests an iatrogenic cause. Based on our experience and the product labeling, clinicians should be more aware of the blood glucose-altering effects of gatifloxacin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 6 publications
(13 reference statements)
0
18
0
Order By: Relevance
“…1,2) However, after clinical introduction in 1999, many serious glycemic abnormalities associated with use of GFLX were reported. [3][4][5][6][7][8] Most of these adverse reactions were observed in diabetic patients, and GFLX is now contraindicated for diabetic patients in Japan and the United States. 6,8) It is known that glycemic control is influenced by a number of drugs.…”
mentioning
confidence: 99%
“…1,2) However, after clinical introduction in 1999, many serious glycemic abnormalities associated with use of GFLX were reported. [3][4][5][6][7][8] Most of these adverse reactions were observed in diabetic patients, and GFLX is now contraindicated for diabetic patients in Japan and the United States. 6,8) It is known that glycemic control is influenced by a number of drugs.…”
mentioning
confidence: 99%
“…Neither hyperglycemia, nor hypoglycemia, 15,16 which is considered to develop by an increase of insulin release, was observed.…”
Section: Discussionmentioning
confidence: 90%
“…Antibiotics, especially fluoroquinolones (gatifloxacin, levofloxacin, etc), have been reported to cause abnormalities in blood glucose homeostasis, such as hypoglycemia and hyperglycemia [2][3][4][5]8]. In vitro studies showed that some fluoroquinolones can block ATP-sensitive potassium channels of pancreatic β-cells and stimulate insulin secretion, leading to hypoglycemia [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotics, especially the fluoroquinolones, have been reported to be associated with alterations in glycemic control among patients with diabetes as well as those without diabetes [2][3][4][5]. However, cephem or macrolide antibiotics have rarely, if ever, been reported to induce hyperglycemia.…”
Section: Introductionmentioning
confidence: 99%